2017
DOI: 10.1061/(asce)as.1943-5525.0000658
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis of a Large-Scale Cycloidal Rotor in Hovering Conditions

Abstract: In this work, four key design parameters of cycloidal rotors, namely the airfoil section, number of blades, chord-to-radius ratio, and pitching axis location, are addressed. The four parameters, which have a strong effect on rotor aerodynamic efficiency, are analyzed with an analytical model and a numerical approach. The numerical method, which is based on a finite-volume discretization of two-dimensional unsteady Reynolds averaged Navier-Stokes equations on a multiple sliding mesh, is proposed and validated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…However, there is still a lot of parameters which may affect the improvement of this characteristic, such as: According to the literature survey (see e.g. [3]), the optimization of the proposed design for obtaining better CRF performance is necessary and it is planned in the future. To this end, the prepared CFD model will be employed together with experimental investigation of the optimized design.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a lot of parameters which may affect the improvement of this characteristic, such as: According to the literature survey (see e.g. [3]), the optimization of the proposed design for obtaining better CRF performance is necessary and it is planned in the future. To this end, the prepared CFD model will be employed together with experimental investigation of the optimized design.…”
Section: Discussionmentioning
confidence: 99%
“…Although both 2D and 3D simulation models can produce results with good accuracy in hovering status, 16,20 2D and 3D models have not been tested and compared in forward flight status. Therefore, both 2D and 3D numerical simulations based on the incompressible unsteady solver were performed.…”
Section: Numerical Simulation Modelmentioning
confidence: 99%
“…Xisto et al. 16 performed parametric analysis on the effects of the parameters of a large-scale cycloidal rotor. They concluded that the best chord to radius ratio is 0.5 and the best location of the blade pitching axis is 0.35C from the leading edge.…”
Section: Introductionmentioning
confidence: 99%
“…Cycloidal rotor is an attractive propulsion system for a wide range of aircraft applications. This type of propulsion system has very good maneuverability for various flight conditions, including hovering, and is mainly dedicated to vertical take-off and landing (VTOL) aircrafts [1] [4]. It was experimentally proved that besides good aerodynamic performance the cycloidal rotor produces little aerodynamic noise, what may be promising in terms to use it for fans.…”
Section: Introductionmentioning
confidence: 99%
“…It was experimentally proved that besides good aerodynamic performance the cycloidal rotor produces little aerodynamic noise, what may be promising in terms to use it for fans. So far several analytical models were developed [4] [5] [6] which to-gether with experimental investigations were helpful in design process of cycloidal rotors. However, currently, the Computational Fluid Dynamics (CFD) allows to take into account unsteady phenomena and it is willingly used in design and analysis of the operation of the cycloidal rotor of various configurations [7] [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%